Prevalence and phylogenetic analysis of porcine circovirus type 2 (PCV2) and type 3 (PCV3) in the Southwest of China during 2020–2022 - Yang, Yanting; Xu, Tong; Wen, Jianhua; Yang, Luyu; Lai, Siyuan; Sun, Xiangang; Xu, Zhiwen; Zhu, Ling (Frontiers in Veterinary Science, 2022)
Porcine circovirus type 2 (PCV2) is considered one of the viruses with substantial economic impact on swine industry in the word. Recently, porcine circovirus type 3 (PCV3) has been found to be involved in porcine dermatitis and nephropathy syndrome (PDNS)-like disease. And the two viruses were prone to co-infect clinically. To further investigate the epidemic profile and genetic diversity of the two viruses, a total of 257 samples from swine at various growth stages suspected for PCVAD on 23 different pig farms between 2020 and 2022 were analyzed for presence of PCV2 and PCV3 by real-time PCR assays. Results showed high prevalence of PCV2 and PCV3: 26.46% samples were PCV2 positive and 33.46% samples were PCV3 positive. The coinfection rate was doubled from 2020 (5.75%) to 2022 (10.45%). Subsequently, the whole genome sequences of 13 PCV2 and 18 PCV3 strains were obtained in this study. Of these, 1 PCV2 strains belonged to PCV2a, 5 belonged to PCV2b and 7 belonged to PCV2d, indicating PCV2d was the predominant PCV2 genotype circulating in the Southwest of China. The phylogenetic analysis of PCV3 showed high nucleotide identity (>98%) among sequences obtained in this study and reference sequences. And 3 mutations (A24V, R27K and E128D) were found in PCV3 antibody recognition domains, which might be related to the mechanism of viral immune escape. Thus, this study will enhance our understanding of the molecular epidemiology and evolution of PCV2 and PCV3, which are conducive to the further study of the genotyping, immunogenicity and immune evasion of PCVs.